"Kemah Allah" sebagai ekspansi akhir Eden dalam langit dan bumi baru - Hauw, Andreas; Emmanuella, Widayanti (KURIOS, 2023)
The aesthetic narrative of the restoration of the cosmic order generally correlates with the human desire for a life without mourning and death. At least, the narrative of the new heavens and the new earth (Rev. 21:1-4) states the same motif. However, the actual depiction of the end times narrated in the culture often excludes the gospel message so that the meaning of human life rests on a permissive public utopia. These narratives convince cognition and captivate the public imagination, including believers. In response to these issues, this paper tries to re-explain the aesthetics narrative of the restoration in the Bible, which is communicated through the metaphor of God’s tabernacle (Rev. 21:3). Along with this presupposition, symbols are lenses for understanding the truth, redemption history is seen as the revelation of the whole meaning of God's tabernacle. For this reason, this article concludes that in light of the redemption history, God’s Tabernacle confirms His presence among the people according to the scheme of the universe's beginning. Thus, life without mourning and death can be understood as a consequence of the fulfillment of God's promise regarding Eden's expansion. In other words, the aesthetic narrative of restoring the cosmic order lies in the relationship between God and man for eternity. Finally, this article is expected to help believers to take responsibility for their faith and to act on it in everyday life. AbstrakEstetika narasi restorasi tatanan kosmis umumnya berkorelasi dengan hasrat manusia akan kehidupan tanpa ratap tangis dan kematian. Setidaknya, narasi langit dan bumi baru (Why. 21:1-4) terlihat menyatakan motif yang senada. Namun, sesungguhnya penggambaran akhir zaman yang dinarasikan dalam budaya kerap mengucilkan berita Injil sehingga makna kehidupan manusia bertumpu pada utopia publik yang permisif. Pasalnya narasi-narasi tersebut tidak hanya menyakinkan kognisi, tetapi menawan imajinasi publik tidak terkecuali orang percaya. Menanggapi hal tersebut, tulisan ini mencoba menguraikan kembali estetika narasi restorasi Alkitab yang dikomunikasikan melalui metafora kemah Allah (Why. 21:3). Bersamaan dengan praanggapan bahwa simbol merupakan lensa untuk memahami kebenaran, sejarah penebusan dinilai menyingkapkan makna inti kemah Allah secara utuh. Untuk itu artikel ini menyimpulkan bahwa dalam terang sejarah penebusan, kemah Allah menegaskan kehadiran Allah di tengah umat sesuai dengan skema awal mula semesta diciptakan. Dengan demikian, kehidupan tanpa ratap tangis dan kematian dapat dipahami sebagai konsekuensi penggenapan janji Allah mengenai ekspansi Eden. Dengan kata lain, estetika narasi restorasi tatanan kosmis terletak pada relasi Allah dan manusia dalam kekekalan. Artikel ini diharapkan dapat menolong orang percaya tatkala mempertanggung jawabkan iman serta mengambil sikap dalam kehidupan sehari-hari.